THE LEARNING PROCESS THROUGH SOCIAL MEDIA FOR CHILDREN: THE ISSUES AND CHALLENGES OF CHILDREN’S FUTURE - Andi Holilulloh; Ben-Naouar Youssef (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2020)
The paper focuses on the influences of Social Media for human’s life which becomes literally hot news between impact and its importance, the children get to communicate freely and also they can feel all aspects from social media. In this globalization era, if social media is usually used without controlling, especially for children, the children are actually victims of social media, although they are mostly smart students and they are studying lots of sciences through high technology that started from elementary school until university level, they would be an educated people. The Technology is normally more suitable that can be used by adult people, both mobile phone or laptop which are easily connected into social media, by using of application and also access which are easy to connect all access around the world until Social Media could change directly the positive mentality of children into negative aspect. The value of this study indicates that social media could give positive impacts such as giving and sharing knowledge, information and learning aspects, but it could give negative impacts at the same time such as making the children anti-social, spreading hoax news, pornography, unkind news and negative information. The survey from APJII (Asosiasi Pengguna Jasa Internet Indonesia) shows that the user of internet within high intensity is to get a better quality of education level. It means that high educated person will always access internet constantly and goodly. Kandell said the students are the community that are greedy to have the internet access compared other communities because the students are in emerging adulthood level that young people get puberty era and change into mature time and they will experience psychological dynamics.